The biology of peatlands - Rydin, Håkan; Jeglum, J. K. (Biology of habitats., 2013)
Peatlands form important landscape elements in many parts of the world and play significant roles for biodiversity and global carbon balance. This new edition has been fully revised and updated, documenting the latest advances in areas such as microbial processes and relations between biological processes and hydrology. As well as thoroughly referencing the latest research, the authors expose a rich older literature where an immense repository of natural history has accumulated. The Biology of Peatlands starts with an overview of the main peatland types (marsh, swamp, fen, and bog), before exa.